Lo Stato cellulare e i suoi cittadini: metafore bio-politiche sulla questione dell’individualità cellulare - Valeria Maggiore (Aisthesis, 2014)
The concept of cell, more than any other biological concept, has been modelled on three powerful metaphors: in a morphological perspective, the cell has been defined Baustein, the brick or elementary unit of the body; from the physiological point of view, it has been associated to a chemical laboratory and finally, in a systemic view, it has been compared to the citizen of the cellular state. The pathologist Rudolf Virchow and the zoologist Ernst Haeckel showed the philosophical and aesthetic potential of the latter metaphor, opening two different perspectives on a crucial problem in the science of living: the problem of the definition of biological individual.